(untitled) (Baghdad Science Journal, 2024)
In the contemporary digital landscape, the imperative issue of data security continues to be a prominent concern. Numerous encryption systems have faced challenges stemming from their intricate nature and susceptibility to cyber threats. This study introduces Cypher-X, an advanced encryption and decryption system that adeptly integrates classical algorithms, namely RSA and Vigenère, to fortify data confidentiality. This research endeavors to address prevailing concerns by focusing on three primary objectives: augmenting data security measures, evaluating system efficiency, and identifying vulnerabilities exploited by cyber adversaries. The outcomes of our investigation affirm the robust encryption capabilities of Cypher-X, underscoring its potential for further enhancement through the incorporation of multi-factor authentication and access control mechanisms. In the realm of data security, Cypher-X emerges as a beacon of hope, offering a promising solution to safeguard sensitive information in the digital sphere. It is essential to acknowledge the ongoing necessity for elucidating our research question, methodology, key findings, and practical implications as we navigate the complex landscape of data protection.